PERANAN IKATAN REMAJA MASJID NURUL UMMAH DALAM MENINGKATKAN KESADARAN BERAGAMA BAGI REMAJA KP. CIKARAWANG DESA TEGALWARU KEC. CIAMPEA - Muhammad Rai Abdilah; Ahmad Mulyadi Kosim; Suyud Arif (KOLONI, 2022)
The purpose of this study was to find out how the efforts of teenagers from the Nurul Ummah Mosque in increasing religious awareness for adolescents in Kp. Cikarang. To find out the influencing factors in increasing religious awareness for adolescents in Kp. Cikarang. This study uses a qualitative approach. The research method, which is based on postpositivism or entrepreneurial philosophy, is used to examine the condition of natural objects, where the researcher is the key instrument, the data collection technique is done by triangulation (combined observation, interviews, documentation), the data obtained tend to be qualitative data, analysis the data is inductive/qualitative, and the results of qualitative research can be in the form of finding potential and problems, uniqueness of objects, meaning of an event, processes and social interactions, certainty of data truth, construction of phenomena, findings of hypotheses. The findings of this study indicate that in increasing religious awareness, the youth of the Nurul Ummah mosque try to provide an interesting forum or study to increase religious awareness for youth in Kp. Cikarawang so that the teenager can uphold Islamic sciences properly and correctly. The importance of the role of the environment can also affect religious awareness for adolescents. Even if it all comes back to you. However, the encouragement and motivation from parents is also important. Therefore, the efforts made by mosque youth are to communicate with each other and invite youth to follow every existing program. Keywords: Role, Mosque Youth, Religious Awareness.